PELATIHAN PIDATO BAHASA INGGRIS BAGI MAHASISWA AKADEMI KEBIDANAN TAHIRAH AL BAETI BULUKUMBA - Indra Irnanda Reseki; Sri Ningsih (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2021)
For Tahirah Al Baeti Midwifery Academy Bulukumba, competing in an English speech competition is still an obstacle due to the lack of student readiness. This service program tries to provide an initial solution by holding English speech training. Within two days, the training was held using a mentoring method and centered on student training. The assistance was assisted by three students of the DIII Midwifery Study Program at the Tahirah Al Baeti Bulukumba Midwifery Academy to become facilitators. Fourteen students participated in the training and were divided into five groups, each accompanied by one student. Lecturers provide material and feedback on student practice, as well as oversee the course of mentoring. In two days, students learn and practice the pronunciation of speech scripts, articulations, and body language needed in making speeches. They also practice speeches in front of the class at the second meeting. The results achieved were that students seemed more confident and motivated to learn to make speeches which were also seen from the results of the evaluation through the questionnaires they filled out. However, it can be concluded that the two-day training has not been maximal in improving language and speech skills. The implication that can be drawn is the need for more intensive training, in a longer time, and with a more pleasant atmosphere that still needs to be developed.